2016
DOI: 10.1063/1.4964312
|View full text |Cite
|
Sign up to set email alerts
|

BN/BNSiO2 sputtering yield shape profiles under stationary plasma thruster operating conditions

Abstract: Quartz Crystal Microbalance (QCM) is used to measure the volumetric and total sputtering yield of Boron Nitride (BN) and Boron Nitride Silicon Dioxide (BNSiO2) bombarded by Xenon ions in the energy range of 100 eV to 550 eV. Sputtering yield shape profiles are reported at various angles of incidence 0-85° with surface normal and compared with modified Zhang model. The yield shape profile is found to be symmetric at normal incidence and asymmetric at oblique incidence. Both the materials show a sudden jump in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…For the sputtering model, the recent experimental measurements of Xe ions impacting on Borosil at room temperature (300 K) by Ranjan et al [13] were selected.…”
Section: Sputtering Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…For the sputtering model, the recent experimental measurements of Xe ions impacting on Borosil at room temperature (300 K) by Ranjan et al [13] were selected.…”
Section: Sputtering Modelingmentioning
confidence: 99%
“…Figures 8 and 9 report, respectively, the dependence of sputter yield on energy and angle, as measured by Ranjan et al [13] compared to those collected by Garnier et al [32], whose data were widely used to built the sputtering models available in the open literature (cfr. Appendix A).…”
Section: Sputtering Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…𝑌 𝜃 is a normalized quantity relative to the case of normal incidence. Several studies have shown that 𝑌 𝜃 generally increases as the incident angle of the impact ion increases, and 𝑌 𝜃 has a peak when the incident angle is around 45-80 deg [19,20]. In the thruster operation with the magnetic screens, the axial acceleration inside the channel was negligible compared with the radial acceleration due to the potential drop in 𝑉 d toward the guard rings, concerning the ions colliding with the walls.…”
Section: Wall Erosion Analysismentioning
confidence: 99%